AB0069 Increased expression of soluble mic-a in the synovial fluid of rheumatoid arthritis patients. (12th June 2018) - Bernardi, L.; Mariotte, A.; Scanu, A.; Noël, D.; Punzi, L.; Bahram, S.; Georgel, P.; Sibilia, J.
Abstract : Background: MIC-A (Major histocompatibility complex class I chain-related gene A) 1 is a transmembrane or soluble protein that interacts with the activating NKG2D receptor. MIC-A stimulates effector responses mediated by NK and CD8 +T cells under cellular stress conditions, like cancer or infections. 2 MIC-A is also associated with autoimmune diseases (such as rheumatic disorders) characterised by immune dysregulation triggered by environmental factors, and plays important roles in immune activation and surveillance. 3 In mice, various NKG2D ligands were discovered: Rae-1, H60 and MULT1 families. 4 Objectives: This study aims at investigating the potential pathological relevance of soluble MIC-A (sMIC-A) protein in inflammatory rheumatic diseases involving articular structures in humans. The expression of orthologous NKG2D ligands in mouse models of experimental joint inflammation is also quantified. Methods: We collected synovial fluid (SF) from 118 subjects: 22 Rheumatoid Arthritis (RA), 13 Psoriatic Arthritis (PSOA), 12 Gout Disease (GOUT), 18 Calcium Pyrophosphate Deposition Disease (CPPD), 8 Reactive Arthritis (REA) and 45 Osteoarthritis patients. Gout and CPPD diseases were confirmed by the presence of crystals in SF. Clinical data were collected. The concentration of soluble MIC-A (sMIC-A), interleukin (IL)−1, IL-6 and IL-8 was measured by ELISA. Murine Rae-1, H60 and Mult1 transcripts were quantified by real-time quantitative PCR (RT-qPCR) in 3 models of joint inflammation: Serum Transfer Arthritis (STA), Collagen-induced arthritis (CIA) and Collagenase-Induced Osteoarthritis (CIOA). Results: Significantly higher levels of sMIC-A were found in the synovial fluid of RA patients in comparison with all others diseases (p<0.001, figure n.1). sMIC-A levels were correlated to white blood cell counts and levels of inflammatory cytokines IL-1, IL-6 and IL-8. Similarly, higher expression levels of Rae-1, H60 and Mult1 were found in chronic arthritis mouse models in comparison with osteoarthritic mice. Conclusions: Our data identifies synovial sMIC-A as an important player in rheumatoid arthritis compared to other rheumatic diseases and osteoarthritis. Investigations in mouse models are in agreement with this finding References: [1] Bahram, Seiamak, et al. A second lineage of mammalian major histocompatibility complex class I genes. Proceedings of the National Academy of Sciences1994;91(14):6259–6263. [2] Groh, Veronika, et al. Costimulation of CD8αβ T cells by NKG2D via engagement by MIC induced on virus-infected cells. Nature immunology2001;2(3):255. [3] Spear, Paul, et al. NKG2D ligands as therapeutic targets. Cancer Immunity Archive2013;13(2):8. [4] Carapito, Raphael, Seiamak, Bahram. Genetics, genomics, and evolutionary biology of NKG2D ligands. Immunological reviews2015;267(1):88–116. Disclosure of Interest: None declared